ASSOCIATION OF BLOOD PRESSURE WITH ALBUMINURIA AND LEFT VENTRICULAR HYPERTROPHY IN YOUNG, MIDDLE AND OLDER AGE GROUPS OF PATIENTS. (April 2021) - Zhang, Wei; Liu, Chang-Yuan; Ji, Li-Nong; Wang, Ji-Guang
Abstract: Objective: We investigated the association of blood pressure with albuminuria and left ventricular hypertrophy (LVH) in young, middle and older age groups of patients. Design and method: Our study participants were treated patients with hypertension or diabetes, enrolled in a China nationwide registry. The 2510 patients were classified into young (<45 years, n = 345), middle (45–65 years, n = 1383) and older (>65 years, n = 782) age groups. Clinic blood pressure was measured three times consecutively on each of the two planned clinic visits. These six readings were averaged for statistical analysis. Albuminuria was defined as a urinary albumin-to-creatinine ratio of > 30 mg/g. LVH was assessed by the electrocardiogram (ECG) Cornell product method. Results: The prevalence of albuminuria and ECG-LVH was 17.8% and 3.7%, respectively, in all patients and 18.1% and 4.2%, respectively, in 2026 (80.7%) patients on antihypertensive medication. The mean (±SD) systolic/diastolic blood pressure was 132.0 ± 16.5/85.2 ± 11.9 mmHg, 136.8 ± 17.9/81.7 ± 11.2 mmHg, and 139.8 ± 16.7/75.8 ± 10.4 mmHg in young, middle and older age groups. In the young age group, the prevalence of albuminuria increased from 8.8% in blood pressure < 120/80 mmHg to 14.6%, 16.0% and 16.5% in blood pressure at 120–130/80–85, 130–140/85–90 and > 140/90 mmHg. The corresponding values were 8.9%, 7.0%, 18.1% and 22.2%, respectively, in the middle age group, and 21.2%, 15.5%, 16.4% and 24.4%, respectively, in the older age group. The prevalence of ECG-LVH was slightly but non-significantly (P for trend > 0.09) higher with increasing blood pressure similarly in all age groups. Conclusions: The relationship between blood pressure and organ damage seems to be age-dependent for albuminuria but not ECG-LVH.